India’s Green Revolution: Fact and Fallacy - Das, S. K.; Tripathi, H. (International Journal of Bio-resource and Stress Management, 2014)
In independent India the first remarkable attempt to agri-rural development has been popularly referred to as ‘green revolution’. This strategy of agri-rural development was based on the idea that traditional agriculture is rain-fed, inefficient and low productive unable to meet the ever rising demand of growing population. Thus, the idea to increase agricultural food production originated from the phenomena of consecutive famines occurred in many parts of India during 1940s. However, diffusion of agricultural innovation of green revolution has brought many undesirable consequences in rural society. Therefore, there is no valid reason to cheer so much about the monumental increase in food grain production. Mere increase in production is not the panacea for all rural social problems. Without a reform in agricultural tax policy, land ownership, credit service, structure and function of society and above all a desirable change in the mind-set of people, policy makers and politicians, no technology, innovation, practice and idea can bring prosperity in rural India. This paper throws light on some of the less discussed issues of India’s famous green revolution which must be taken into consideration before kick starting a second green revolution or evergreen revolution based on genetically modified crops, nano-technology, biotechnology, system of rice intensification (SRI), or ground water irrigation, and so on.